(untitled) (Research, Society and Development, 2021)
Palliative care (CP) is characterized as active care that encompasses the body, mind and spiritual issues. In pediatrics they are often used for patients in severe health and life-limiting conditions such as cancer. Due to the complexity and the long period of treatment, professionals face some barriers to providing quality care, specifically the nurse, as the professional responsible for patient care. The aim of the study is to investigate through scientific evidence the challenges of the role of nurses in the oncopediatric patient undergoing palliative care. The integrative research method was used, where 16 articles available in full from 2015 to 2020, selected from the Virtual Health Library VHL, are part of the analyzed sample. The results showed the main difficulties in the provision of PC, with the majority being questions related to education. It is concluded that there is a great need for investment and updates in the training and clinical practice of nursing professionals.